All roads lead to Rome the creation, context and transmission of the Codex Amiatinus - Hawkes, Jane; Boulton, Meg (Brepols, 2019)
"The Codex Amiatinus is perhaps the most famous copy of the Bible surviving in Western Europe. A fascinating and elusive manuscript, with a suite of decorated folios, it was made in Anglo-Saxon England around the turn of the eighth century at the twin monastic foundation of Wearmouth and Jarrow as one of three such 'pandects'. Created at the monastic foundation celebrated in the work of the Venerable Bede, this vast and luxe manuscript was sent by the Northumbrian monks as a gift to the Pope in 716 and, after a sojourn of some 900 years at Monte Amiato (Tuscany), it was donated to the Biblioteca Medicea Laurenziana in Florence in the eighteenth century. As a result of an international conference held to commemorate the 1300th anniversary of the departure of the manuscript from Northumberland and coinciding with the production and presentation of a facsimile of the Codex to the Museum at Jarrow, this volume - the first devoted to the Codex Amiatinus - brings together twelve essays that offer a new appraisal of this remarkable book, and of the contexts that surrounded its production. Encompassing its text, its images, its social, political and ecclesiastical contexts and its later medieval legacy, the contributions to this volume highlight several previously unrecognised aspects and details of the manuscript that further our understanding of the Codex as a book, and as inheritor and progenitor of manuscript traditions in its own right."
Keywords: Codex Amiatinus; Konferenzschrift -- 2016